Edge Activator: Effect of Concentration Variation of Tween 80 on Characteristics and Rate of Difusion transfersome sodium diclofenac - Gabena Indrayani Dalimunthe; Ricky Andi Syahputra (State University of Gorontalo, 2021)
Diclofenac sodium is a Transfersom is a transdermal delivery system consisting of phospholipids and edge activators. Transfersom increases the size of the stratum corneum lipid barrier pores, then enters the skin through the drive of the trans-barrier motion and squeezes itself to follow the lipid barrier pore size. The purpose of this study is to determine the effect of the tween-80 concentration as an edge activator on the characteristics and diffusion rate of diclofenac sodium transfersom. Transferom preparation used the vortex-sonication method which was made in five formulae with variations in the concentration ratio of phosphatidylcholine and tween-80 (95:05, 90:10, 85:15, 80:20, and 75:25). The results show that all five formulae have different morphological forms. The results of statistical tests using One-Way ANOVA finds a significant effect (p-value) of the edge activator concentration on the diffusion rate of diclofenac sodium transfersom.